Clinico-microbiological profile and antibiotic sensitivity pattern of chronic suppurative otitis media with cholesteatoma - Janvi Bhavsar; Rachana Prajapati; Jayman Raval; R. G. Aiyer (The Egyptian Journal of Otolaryngology)
Abstract Background To determine microbiological profile (Aerobic, Anaerobic, and Fungal) and antibiotic sensitivity pattern in isolated microbes in Chronic Suppurative Otitis Media (CSOM) with cholesteatoma. This prospective study had been done at tertiary level hospital & medical college in Western part of India for one and a half year. 55 number of patients, who were diagnosed as active CSOM with cholesteatoma clinically or in HRCT temporal bone were included. Samples of ear discharge & cholesteatoma were sent to microbiology laboratory for the isolation of organisms & then studied for the antibiotic sensitivity pattern. Postoperatively follow up was carried out at 1st, 2nd, and 3rd months looking for cavity after giving antibiotic to pattern as per sensitivity. Results Among 42 (76.36%) bacterial isolate, Pseudomonas Spp. 19 (34.54%) was the predominant bacteria; followed by Staphylococcus Aureus 07(12.72%) & Proteus Mirabilis 04 (7.27%). Pseudomonas was sensitive to antibiotics- Levofloxacin (84.21%), Imipenem (68.42%), Cefepime (68.42%), Ceftazidime (57.89%). Conclusions Pseudomonas Aeruginosa was the most common aerobic bacteria isolated in this study, followed by Staphylococcus Aureus. While, anaerobic bacteria isolated in present study was Bacteroides and fungus was Aspergillus Niger. Pseudomonas Aeruginosa showed highest susceptibility for Levofloxacin followed by Imipenem, Cefepime, Ceftazidime and high resistance against Co-trimoxazole and Ampicillin. Though the treatment of CSOM with cholesteatoma is surgical, pre-operative isolation of organisms and their drug sensitivity pattern will not only improve cavity healing but also help in prevention of resistant strain and complications.